Atorvastatin Pleiotropism: Role in Cardioprotection - Rohilla, Ankur (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTThe 3-hydroxymethyl-glutaryl coenzyme A (HMG-CoA) reductase inhibitors, known as statins, are known to be the prime and most effective therapy for reducing blood cholesterol levels and hence, significantly reduce cardiovascular morbidity and mortality. Moreover, statins possess a wide range of beneficial biological effects apart from lipid lowering commonly referred to as the pleiotropic effects. Atorvastatin, a member of statins, has been used for lowering blood cholesterol levels by inhibiting HMG-CoA reductase. Atorvastatin has been well reported to be an effective drug therapy for the treatment of dyslipidemias alongwith prevention of various cardiovascular diseases. The present review article summarizes about the numerous pleiotropic effects exhibited by atorvastatin in affording cardioprotection.